Mefâtîhu’l-gayb - 880-01 Fahreddin er-Râzî, 1149-1210. (Bulak)
9 cilt (1. c. 756 sayfa ; 2. c. 743 sayfa ; 3. c. 804 sayfa ; 4. c. 556 sayfa ; 5. c. 832 sayfa ; 6. c. 806 sayfa ; 7. c. 826 sayfa ; 8. c. 775 sayfa ; 9. c. [194] sayfa)